Hubungan Antara Kadar Laju Endap Darah (LED) Dengan Kadar C-Reaktiv Protein (CRP) Pada Penderita Tuberkulosis (TBC) Di Wilayah Kerja Puskesmas Alas Barat - aini aini aini; Nurmawan Nurmawan; Jumari Ustiawaty (Poltekkes Kemenkes Mataram, 2020)
Tuberculosis is a disease caused by rod-shaped bacteria (basil) with another name Mycrobacterium tuberculosis. Mycrobacterium tuberculosis enters the body then causes inflammation, inflammation and bacterial invasion which then induces liver cells to synthesize acute phase C-reactive protein protein (CRP). CRP will increase sharply after inflammation, as well as the formation of aggregates derived from the acute phase protein hormone which causes an increase in the Erythrocyte sedimentation rate (ESR)). The purpose of this study was to determine the relationship Erytrocyte sedimentation rate (ESR) and levels of C-Reactiv protein (CRP) in tuberculosis (TBC) patients. This research is an analytical descriptive study using cross sectional. Data collectors are done using the Non Random Accidental Sampling technique. The number of respondents in this study were 11 people with tuberculosis. Based on the results of this study it is known that TBC patients with smear negative as much as 7 people (63.6%) and TB patients with positive smear as much as 4 people (36.4%), both in TB patients with negative smear and positive smear both have levels of ESR not normal with an average ESR level in positive smear of 101.3 mm / hour and the average ESR level in smear negative is 20.8 mm / hour. All TBC patients with smear positive CRP levels (not normal) with an average mean value of CRP of 36 mg / L or an average CRP level in TBC smear negative patients of 0.9 mg / L. Based on the Pearson test results between levels of erythrocyte sedimentation rate (ESR) with C-Reactive protein (CRP) in tuberculosis (TBC) patients obtained a value of p <0.01 (0.000 <0.01). This shows a strong relationship between LED and CRP levels in TB patients